Stent for Life project: present situation in Turkey. - Göktekin, Ömer; Ertaş, Gökhan; Kervan, Ümit; Koç, Orhan; Kozan, Ömer (My University, 2012)
The rate of percutaneous coronary intervention for acute ST-segment elevation myocardial infarction varies between European countries. The variations arise partly because of differences between countries in the primary percutaneous coronary intervention network system. The lack of an organised primary percutaneous coronary intervention network system in Turkey was the main reason for the low rate of primary percutaneous coronary intervention in Turkey. The Stent for Life project has increased the awareness of the importance of the prompt treatment of ST-segment elevation myocardial infarction in our country. Primary percutaneous coronary intervention has emerged as the preferred reperfusion strategy for patients with ST-segment elevation myocardial infarction in pilot cities after three years of Stent for Life project. In the present manuscript, we aim to summarise the current situation and the targets of the Stent for Life project in Turkey.